2021
DOI: 10.3390/diagnostics11112057
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Imaging of Invasive Fungal Disease in Immunocompromised Hosts

Abstract: Invasive fungal disease (IFD) leads to increased mortality, morbidity, and costs of treatment in patients with immunosuppressive conditions. The definitive diagnosis of IFD relies on the isolation of the causative fungal agents through microscopy, culture, or nucleic acid testing in tissue samples obtained from the sites of the disease. Biopsy is not always feasible or safe to be undertaken in immunocompromised hosts at risk of IFD. Noninvasive diagnostic techniques are, therefore, needed for the diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 141 publications
(225 reference statements)
0
6
0
Order By: Relevance
“…To further reveal the important impact of the F 1 F o -ATP synthase α subunit on host inflammatory responses, according to the fact that the uptake and accumulation of [ 18 F]FDG in active inflammatory cells was obviously higher than that in normal cells [ 47 ], microPET/CT combined with radioactivity measurement by γ-counting [ 48 ] was used to monitor the inflammatory response in tissues and organs – especially the kidney, the target organ of IC [ 17 ]—in infected mice. The microPET/CT imaging displayed that the uptake of [ 18 F]FDG in the systemic organs of atp1 Δ/Δ-infected mice had no difference from that in NS-control mice, while was obviously decreased compared with that in WT-infected mice ( Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…To further reveal the important impact of the F 1 F o -ATP synthase α subunit on host inflammatory responses, according to the fact that the uptake and accumulation of [ 18 F]FDG in active inflammatory cells was obviously higher than that in normal cells [ 47 ], microPET/CT combined with radioactivity measurement by γ-counting [ 48 ] was used to monitor the inflammatory response in tissues and organs – especially the kidney, the target organ of IC [ 17 ]—in infected mice. The microPET/CT imaging displayed that the uptake of [ 18 F]FDG in the systemic organs of atp1 Δ/Δ-infected mice had no difference from that in NS-control mice, while was obviously decreased compared with that in WT-infected mice ( Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…Some comprehensive reviews have discussed the role of FDG PET/CT in IFD in the immunocompromised host, in children and monitoring therapy. 18,29,30 This review discusses the added value of FDG PET/CT to other imaging modalities used in evaluating FDG PET/CT.…”
Section: Pet/ct Imaging and Ifdmentioning
confidence: 99%
“…FDG PET/CT is a non-invasive marker of disease and standard uptake value, and other metabolic indices provide a semi-quantitative measure of the disease activity within lesions. This allows longitudinal followup of IFD lesions over time, 19,29,30,72 Again, the earlier physiological FDG PET data changes may detect response to antifungal therapy earlier than other morphological images in response to antifungal treatment. In a study from a single Medical Centre in the Netherlands, FDG PET/CT was found to have altered the treatment of IFD in 50% of patients leading to the cessation, switch in antifungal therapy or increase in the dose of antifungal therapy.…”
Section: Monitoring Of Antifungal Therapymentioning
confidence: 99%
“…This dynamism afforded by molecular imaging techniques makes the characterization of the biological behavior and metabolic pathways that drive diseases, including TB, possible. 29,30 Radionuclide Imaging of Tuberculosis: The Possibilities Radionuclide imaging techniques have been applied in interrogating the various aspects of Tb, including disease diagnosis, lesion characterization, disease evolution, treatment response assessment, prognostication, relapse prediction, and pharmacokinetic study of current and novel anti-TB drugs. 20,21,31,32 This array of applications of radionuclide imaging techniques explored in studying TB infection and disease in humans and laboratory animals has advanced the knowledge regarding the disease.…”
Section: The Tuberculous Granuloma At the Crux Of The Mattermentioning
confidence: 99%